Flax rhamnogalacturonan lyases: phylogeny, differential expression and modeling of protein structure. Issue 2 (21st December 2018) - Mokshina, Natalia; Makshakova, Olga; Nazipova, Alsu; Gorshkov, Oleg; Gorshkova, Tatyana
Abstract : Rhamnogalacturonan lyases (RGLs; EC 4.2.2.23) degrade the rhamnogalacturonan I (RG‐I) backbone of pectins present in the plant cell wall. These enzymes belong to polysaccharide lyase family 4, members of which are mainly from plants and plant pathogens. RGLs are investigated, as a rule, as pathogen 'weapons' for plant cell wall degradation and subsequent infection. Despite the presence of genes annotated as RGL s in plant genomes and the presence of substrates for enzyme activity in plant cells, evidence supporting the involvement of this enzyme in certain processes is limited. The differential expression of some RGL genes in flax ( Linum usitatissimum L.) tissues, revealed in our previous work, prompted us to carry out a total revision (phylogenetic analysis, analysis of expression and protein structure modeling) of all the sequences of flax predicted as coding for RGLs. Comparison of the expressions of LusRGL in various tissues of flax stem revealed that LusRGLs belong to distinct phylogenetic clades, which correspond to two co‐expression groups. One of these groups comprised LusRGL6‐A and LusRGL6‐B genes and was specifically upregulated in flax fibers during deposition of the tertiary cell wall, which has complex RG‐I as a key noncellulosic component. The results of homology modeling and docking demonstrated that the topology of the LusRGL6‐A catalytic site allowed binding to the RG‐I ligand. These findings lead us to suggest the presence of RGL activity in planta and the involvement of special isoforms of RGLs in the modification of RG‐I of the tertiary cell wall in plant fibers.